2011
DOI: 10.5251/abjna.2011.2.5.860.866
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sudanese native Dwarf and Bare Neck Chicken raised under improved traditional production system

Abstract: A total of 300 indigenous pullets of various ecotypes were used for phenotypic characterization of the native chicken of Sudan. This study aimed at evaluating production performance, egg characteristics and clutch traits of dwarf (Betwil) and Bare Neck ecotypes. Laying rate, average egg weight and egg components weights (albumen, yolk and shell) were significantly lower (P<0.05) in dwarf (Betwil) than in Bare Neck. However yolk : albumen ratio and relative yolk weight were higher in dwarf (Betwil) than in Bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
3
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
2
7
3
1
Order By: Relevance
“…The significant positive correlations between egg weight and egg width observed in indigenous chickens are consistent with previous reports (Yakubu et al, 2008;Yousif and Eltayeb, 2011;Kgwatalala et al, 2016;Markos et al, 2017). Significant and positive correlation coefficients between egg weight and other external egg quality traits, such as egg width, egg length, and shell weight indicate that selection for higher egg weight in indigenous chickens could result in simultaneous positive improvements of the other traits but might negatively influence the shell ratio of local chicken ecotypes that is negatively correlated with egg weight.…”
Section: Correlation Of Egg Quality Traitssupporting
confidence: 92%
“…The significant positive correlations between egg weight and egg width observed in indigenous chickens are consistent with previous reports (Yakubu et al, 2008;Yousif and Eltayeb, 2011;Kgwatalala et al, 2016;Markos et al, 2017). Significant and positive correlation coefficients between egg weight and other external egg quality traits, such as egg width, egg length, and shell weight indicate that selection for higher egg weight in indigenous chickens could result in simultaneous positive improvements of the other traits but might negatively influence the shell ratio of local chicken ecotypes that is negatively correlated with egg weight.…”
Section: Correlation Of Egg Quality Traitssupporting
confidence: 92%
“…Naked neck chickens laid heavier eggs with higher mean length and width than the present white leghorn strain at 40 weeks of age [ 9 ]. There were also reports of lower mean values in comparison to the present findings for egg length (54.39±0.11 mm) and width (39.92±0.07 mm) [ 7 ]. The shape index reported under the study (73.53±0.18) falls within the “normal” range of 72-76 [ 10 ] and is lower than the earlier reports [ 8 , 9 , 11 ].…”
Section: Resultscontrasting
confidence: 67%
“…Yeasmin and Howlider (1998) and Yeasmin et al (2003) where they found hen day egg production of IDC were 33.50 and 43.26%, respectively. Rate of lay of native dwarf chicken of Kenya, Benin and Sudan was 36, 33 and 39.32 % respectively reported by Njenga (2005), Dakpogan et al (2012) and Yousif and Eltayeb (2011), respectively. Findings of these above studies support the present investigation.…”
Section: Introductionmentioning
confidence: 71%